2021
DOI: 10.3389/fimmu.2021.667875
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Alpha Pathway Alternation Predicts Survival of Immune Checkpoint Inhibitors in Non-Small Cell Lung Cancer

Abstract: Translational research on immune checkpoint inhibitors (ICIs) has been underway. However, in the unselected population, only a few patients benefit from ICIs. Therefore, screening predictive markers of ICI efficacy has become the current focus of attention. We collected mutation and clinical data from an ICI-treated non-small cell lung cancer (NSCLC) cohort. Then, a univariate Cox regression model was used to analyze the relationship between tumor necrosis factor α signaling mutated (TNFα-MT) and the prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Chemokines and cytokines secreted by immune cells in TME are important components of LUAD anti-tumor immunity. 46 The ssGSEA results showed that cytokines and chemokine produced pathways related to immunosuppression, such as IL-10, IL-1β, CCL2 and CXCL2, were significantly down-regulated in the BCR signaling MUT group. 47 These factors recruit tumor-associated macrophages (TAMs), Tregs and Myeloid-derived suppressor cells (MDSCs) into the TME, helping tumor cells escape detection by the immune system and promoting the development and metastasis of tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Chemokines and cytokines secreted by immune cells in TME are important components of LUAD anti-tumor immunity. 46 The ssGSEA results showed that cytokines and chemokine produced pathways related to immunosuppression, such as IL-10, IL-1β, CCL2 and CXCL2, were significantly down-regulated in the BCR signaling MUT group. 47 These factors recruit tumor-associated macrophages (TAMs), Tregs and Myeloid-derived suppressor cells (MDSCs) into the TME, helping tumor cells escape detection by the immune system and promoting the development and metastasis of tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Our data provide evidence to support the concept that TNFα signaling reprograms ketone body metabolism, representing a ''wiring'' between metabolism and cell signalling pathways. TNFαmediated chronic inflammation plays an important role in the initiation, metastasis and drug resistance of lung cancer [31][32][33]. Blockade of TNFα signaling can render lung cancer PDXs that express wild-type EGFR sensitive to the treatment of EGFR inhibitors, and improve the therapeutic effect of EGFR inhibitors in lung cancer PDXs with EGFR mutations [32].…”
Section: Discussionmentioning
confidence: 99%
“…These new tumor antigens can not only enhance the immune response of T cells, but also increase the content of new antigen-specific T cells, thus improving the immune system's ability to identify tumors (32). Studies have shown that the mutation of the DDR pathway will result in the production of higher TMB and neoantigen loads, thus significantly improving the effectiveness of ICI treatment (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%